Sustaining student concentration: the effectiveness of micro-breaks in a classroom setting - Sharpe, Benjamin T.; Trotter, Michael Geoffrey; Hale, Beverley J. (Frontiers in Psychology, 2025)
This study investigates the impact of break frequency on students' attention and quiz performance during university classes, grounded in cognitive load theory and the concept of spaced learning. Involving 253 second-year undergraduates, it reveals significant effects of break conditions on performance, with micro-break participants outperforming others and sustaining better performance over time. The study employed a mixed-methods design, comparing traditional break periods with more frequent micro-breaks. Results showed that while performance declined across seminars for both conditions, aligning with vigilance literature, the micro-break condition exhibited more consistent performance. These findings contribute to our understanding of cognitive load management and the spacing effect in educational settings. The study highlights the importance of addressing attention spans in classrooms and suggests that incorporating micro-breaks may enhance students' engagement and academic achievement. Implications for instructional design in higher education are discussed, offering evidence-based strategies for educators to optimize the learning experience.